KANDUNGAN NILAI RELEVANSI DAN KEANDALAN YANG TERDAPAT DALAM INFORMASI ASET TIDAK BERWUJUD - Andry Willy Ponda; Reisanti Edie Wijaya (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
The study of the relevance and reliability in the reporting of intangible assets are still debatable in the academic. Many analysts believe about the role of intangible assets in the company, and even many companies have a greater proportion of intangible assets than intangible assets.This Their paper examines the value relevance and reliability of intangible assets, represented by the influence of equity market value to intangible assets in companies that enrolled in PT BEI period 2004-2007. However, the results of this study was not in line with previous studies outside Indonesia that may be caused by differences between countries economic stability.